(untitled) (Revista Educação, Artes e Inclusão, 2023)
ABSTRACT: This article builds on the work developed with teachers from an English language institute who took a course on Inclusive Education as part of their continuous professional development in 2019. Their main objective was to reflect upon ways of working with their students with specific educational needs. The course was based on Vygotsky’s historical-cultural approach ([1924 – 1934] 1999; [1997] 2012a), and used the Critical Collaboration Research (PCCol) (MAGALHÃES, 1990 - 2020) as a methodological basis for its development. The data presented are based on the discourse produced by teachers during classes. Teachers’ discussions evidenced the importance of arts, mainly films in this case, as a springboard for a better understanding the daily routine of people with specific educational needs. As teachers watched and discussed the movies, they became better able to understand and connect to a reality which is different from theirs, and, as a consequence, it made teacher better understand the impact of their actions in class.